ANALISIS TINGKAT KECEMASAN ATLET HOCKEY KABUPATEN MALANG MENUJU PORPROV JATIM 2025 - Windriyani, Shinta Masitho; Husni, Ahmad Ulul Bisri; Anugraini, Asri Putri (Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi (Penjaskesrek), 2025)
Abstract: Achieving the best performance of athletes in addition to physical, technical and tactical, mental is an important role. Because with good mentality and self-control, it is able to provide excellent physical condition. Mental factors that often appear and interfere with athletes' performance, one of which is anxiety. Therefore, by providing a test to measure anxiety levels, it will be known to what extent the coach's training program is able to have a positive influence on athletes. The research instrument used a questionnaire, with the research subject being carried out on 32 athletes in Malang Regency hockey athletes. Data analysis was processed using a formula to find the percentage number of anxiety levels in hockey athletes in Malang district. The results of the data analysis stated that there were 6 athletes (19%) included in the category of having a high level of anxiety; 10 athletes (31%) had moderate anxiety levels and 16 athletes (50%) were in the low anxiety level category. So with the hope that this research can have a positive impact, especially for coaches to be able to provide motivation for athletes and athletes are able to know the anxiety that exists in a team or individual. Keywords: anxiety and athletesÂ Abstrak: Pencapaian performa terbaik atlet selain fisik, teknik dan taktik, mental merupakan peran penting. Karena dengan mental dan control diri yang baik mampu memberikan kondisi fisik yang prima. Faktor mental yang sering muncul dan mengganggu performa atlit, salah satunya adalah kecemasan. Oleh karena itu dengan memberikan tes pengukuran tingkat kecemasan, maka akan diketahui sejauh mana program latihan dari pelatih mampu memberikan pengaruh positif bagi atlet. Instrument penelitian menggunakan kuesioner, dengan subjek penelitian dilakukan pada atlet hockey Kabupaten Malang sebanyak 32 atlet. Analisis data diolah dengan menggunakan rumus mencari angka persentase tingkat kecemasan pada atlet hockey kabupaten Malang. Hasil dari analisis data dinyatakan bahwa terdapat 6 atlet (19%) termasuk dalam kategori memiliki tingkat kecemasan yang tinggi; 10 atlet (31%) tingkat kecemasan sedang dan 16 atlet (50%) masuk dalam kategori tingkat kecemasan rendah. Maka dengan harapan dilakukannya penelitian ini mampu memberikan dampak positif terutama bagi pelatih untuk mampu memberikan motivasi bagi atlit serta atlit mampu mengetahui kecemasan yang ada dalam tim atau individu.Kata Kunci: kecemasan dan atlet